2022
DOI: 10.3389/pore.2022.1610558
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Cuproptosis-Related Genes With Clinical Outcomes and the Tumour Immune Microenvironment in Hepatocellular Carcinoma

Abstract: Background: Cuproptosis is a recently identified form of regulated cell death that plays a critical role in the onset and progression of various cancers. However, the effects of cuproptosis-related genes (CRGs) on hepatocellular carcinoma (HCC) are poorly understood. This study aimed to identify the cuproptosis subtypes and established a novel prognostic signature of HCC.Methods: We collected gene expression data and clinical outcomes from the TCGA, ICGC, and GEO datasets, analysed and identified 16 CRGs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The combined datasets encompassed 75 cases of HIRI and 80 control cases. Thirty-eight CRGs were recovered from the previous literature ( ATP7A, ATP7B, ACO2, CDKN2A, DBT, DLAT, DLD, DLST, DPYD, FDX1, GCSH, GLRX5, GLS, ISCA2, LIAS, LIPA, LIPT1, LIPT2, LIPM, MTF1, NDUFA1, NDUFA8, NDUFB10, NDUFB2, NDUFB6, NLRP3, NDUFC1, NDUFC2, NDUFV2, NFE2L2, PDHA1, PLAT, PDHB, POLD1, PPAT, SLC31A1, SDHB, and TIMMDC1 ) ( 11 , 12 ). ATP7A mutations cause Menkes disease, Hence, ATP7A was excluded from further consideration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined datasets encompassed 75 cases of HIRI and 80 control cases. Thirty-eight CRGs were recovered from the previous literature ( ATP7A, ATP7B, ACO2, CDKN2A, DBT, DLAT, DLD, DLST, DPYD, FDX1, GCSH, GLRX5, GLS, ISCA2, LIAS, LIPA, LIPT1, LIPT2, LIPM, MTF1, NDUFA1, NDUFA8, NDUFB10, NDUFB2, NDUFB6, NLRP3, NDUFC1, NDUFC2, NDUFV2, NFE2L2, PDHA1, PLAT, PDHB, POLD1, PPAT, SLC31A1, SDHB, and TIMMDC1 ) ( 11 , 12 ). ATP7A mutations cause Menkes disease, Hence, ATP7A was excluded from further consideration.…”
Section: Methodsmentioning
confidence: 99%
“…This mutation has been reported to potentially involve cuproptosis ( 8 ). Some studies have also hinted at an underlying connection between cuproptosis and other liver diseases such as hepatocellular carcinoma and nonalcoholic fatty liver disease; cuproptosis has also attracted great interest in its therapy ( 11 , 12 ). However, research on the role of copper or cuproptosis in HIRI remains relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…SLC31A1 is equivalent to the input of copper. The inhibition of SLC31A1-dependent copper transport leads to anti-cell-death effects in cancer cells [ 18 ]. Studies have found that the expression of SLC31A1 in liver cancer samples has changed, which is related to the increase in copper content in liver tissues; liver cancer cell lines rely on CTR1 to transport copper for proliferation, colony formation, and growth.…”
Section: Copper Transporter and Iron Transporter In Liver Cancermentioning
confidence: 99%
“…We compared our own model to 12 other published HCC prognostic models to better show its predictive power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Multivariate analysis was used to calculate the risk value and prognostic evaluation for each dataset, leveling the playing field amongst the four models.…”
Section: New Model As a New Predictor Of Hccmentioning
confidence: 99%